2015
DOI: 10.1016/j.urology.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Demographics on Excretion of Key Urinary Factors Related to Kidney Stone Risk

Abstract: Objective To investigate the effect of demographics including age and sex on excretion of four key urinary factors (calcium (Ca), magnesium (Mg), oxalate (Ox) and uric acid (UA)) related to kidney stone risk. Methods Twenty-four hour urine samples were collected from non-Hispanic white sibships in Rochester, MN. Height, weight, blood pressure, serum creatinine and cystatin C (CC) were measured. Diet was assessed using the Viocare food frequency questionnaire. Effects of demographics and dietary elements on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
8
1
4
Order By: Relevance
“…Black men and Hispanic men were 63% and 40% less likely to have a history of KS than White men respectively ( Scales et al, 2012 ). Age was associated with KS ( Perinpam et al, 2015 ; Scales et al, 2012 ). KS prevalence was 10.8% (2007–2010) in men, and varied when stratified by age groups (3.4% for 20–29, 6.9% for 30–39, 9.8% for 40–49, 13.1% for 50–59, and 19.1% for 60–69 years) ( Scales et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black men and Hispanic men were 63% and 40% less likely to have a history of KS than White men respectively ( Scales et al, 2012 ). Age was associated with KS ( Perinpam et al, 2015 ; Scales et al, 2012 ). KS prevalence was 10.8% (2007–2010) in men, and varied when stratified by age groups (3.4% for 20–29, 6.9% for 30–39, 9.8% for 40–49, 13.1% for 50–59, and 19.1% for 60–69 years) ( Scales et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…KS prevalence was 10.8% (2007–2010) in men, and varied when stratified by age groups (3.4% for 20–29, 6.9% for 30–39, 9.8% for 40–49, 13.1% for 50–59, and 19.1% for 60–69 years) ( Scales et al, 2012 ). Increasing age was significantly associated with excretion of key urinary compounds related to kidney stones ( Perinpam et al, 2015 ), and there was a reverse association between total testosterone concentrations and age ( Feldman et al, 2002 ; Harman et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…CKD has also been hypothesized as a risk factor for stone formation in previous studies, thus we chose to evaluate creatinine clearance. Still, 24-hour CrCl was not a strong predictor in our model (Figure 5), contrasting previous studies that demonstrated renal function (eGFR) may affect stone type 2629 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, our results resemble what is reported in the U.S population 18 . While gender influences excretion of key urinary factors related to stone formation 26 , the underlying cause(s) for the rising female KSF proportion over time has not yet been fully elucidated. Nevertheless, the magnitude of the impact of obesity on increasing the risk of KS formation has been reported to be greater in women than in men 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Kidney calculi are classified into five major types: Calcium oxalate (CaOx) -most commonly occurring, calcium phosphate (CaP), uric acid, struvite, and cysteine stones [5,6]. Besides, the fact that these urinary risk factors that are excreted in the urine, such as calcium, uric acid, and cysteine, are higher in men might actually be one major reason hypothesized to be bolstering the demographic findings [7]. Thus, digging further deep into the causative and the modulating factors that affect the disease, the role of the various components of the urine seems one regulatory aspect that cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%